2008
DOI: 10.1016/j.bbamcr.2008.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Androgen regulates Cdc6 transcription through interactions between androgen receptor and E2F transcription factor in prostate cancer cells

Abstract: Androgen receptor plays a critical role in the development and maintenance of cancers in the prostate. Earlier, we have shown that Cdc6, a regulatory protein for initiation of DNA replication, is down regulated in androgen-insensitive prostate cancer cells. In this report, we studied the involvement of androgen, mediated through androgen receptor (AR) in regulation of Cdc6 expression. Our results demonstrated that androgen treatment stimulated Cdc6 expression in xenograft tumors and androgen-sensitive prostate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…Androgen can act through its receptor binding to a 15-bp palindromic androgen response element in the Cdc6 promoter on the transcription of Cdc6 gene in prostate cancer cells (55,68). By qRT-PCR, we showed that Cdc6 expression was significantly increased in the fat body and ovary post adult female eclosion, which are in conformity with the elevated JH titers (50,51).…”
Section: Discussionmentioning
confidence: 61%
“…Androgen can act through its receptor binding to a 15-bp palindromic androgen response element in the Cdc6 promoter on the transcription of Cdc6 gene in prostate cancer cells (55,68). By qRT-PCR, we showed that Cdc6 expression was significantly increased in the fat body and ovary post adult female eclosion, which are in conformity with the elevated JH titers (50,51).…”
Section: Discussionmentioning
confidence: 61%
“…Although the androgen response element (ARE) is not listed among the top transcription factor binding motifs enriched in EZH2 ChIP-seq dataset, we confirmed its significant enrichment in the proximal region of EZH2 solo peaks. It is interesting to note that the Rb/E2F1 pathway has been shown as a critical regulator of AR expression and transcriptional activity (42-44). Although the activator E2Fs are generally believed to have a great deal of functional redundancy, only E2F1 and E2F3 were shown to enhance AR activity, while E2F2 was insufficient for this function (42).…”
Section: Discussionmentioning
confidence: 99%
“…A threshold model was proposed where genes that regulate cell proliferation or apoptosis are induced by different levels of E2F that act as positive or negative regulators of cell growth (53). Positive and negative cooperation in gene regulation by AR and E2F1 were reported in prostate cancer cells (95)(96)(97). Relative levels of MAGE-A11 and p107 influence AR and E2F1 transcriptional activation or repression.…”
Section: Primate-specific Transcriptional Coregulator Mage-a11-mentioning
confidence: 99%